1999
DOI: 10.1126/science.284.5416.962
|View full text |Cite
|
Sign up to set email alerts
|

Functional Selection of Adaptive Auditory Space Map by GABA A -Mediated Inhibition

Abstract: The external nucleus of the inferior colliculus in the barn owl contains an auditory map of space that is based on the tuning of neurons for interaural differences in the timing of sound. In juvenile owls, this region of the brain can acquire alternative maps of interaural time difference as a result of abnormal experience. It has been found that, in an external nucleus that is expressing a learned, abnormal map, the circuitry underlying the normal map still exists but is functionally inactivated by inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 18 publications
6
69
0
Order By: Relevance
“…An important structure within this chain is the midbrain inferior colliculus (IC), because it acts as the primary relay center between ascending projections from the lower brainstem nuclei and ascending projections to the thalamus. Because of its unique makeup of converging ascending and corticofugal projections (Irvine, 1992;Zhang and Suga, 2005), animal studies have identified the IC as a site of both activity-and experience-dependent developmental plasticity in both vertebrate and, most recently, mammalian brains (Brainard and Knudsen, 1993;Knudsen, 1998;Zheng and Knudsen, 1999;DeBello et al, 2001;Yu et al, 2007). However, similar studies on developmental plasticity in the human auditory brainstem have been limited primarily because of the obvious limitations in the use of parallel technique and experimental design.…”
Section: Introductionmentioning
confidence: 97%
“…An important structure within this chain is the midbrain inferior colliculus (IC), because it acts as the primary relay center between ascending projections from the lower brainstem nuclei and ascending projections to the thalamus. Because of its unique makeup of converging ascending and corticofugal projections (Irvine, 1992;Zhang and Suga, 2005), animal studies have identified the IC as a site of both activity-and experience-dependent developmental plasticity in both vertebrate and, most recently, mammalian brains (Brainard and Knudsen, 1993;Knudsen, 1998;Zheng and Knudsen, 1999;DeBello et al, 2001;Yu et al, 2007). However, similar studies on developmental plasticity in the human auditory brainstem have been limited primarily because of the obvious limitations in the use of parallel technique and experimental design.…”
Section: Introductionmentioning
confidence: 97%
“…In some sensorimotor systems, altered sensory experience can shift suprathreshold response patterns, whereas synapses conveying information about previously preferred stimuli are anatomically maintained but functionally suppressed, at least at the suprathreshold level (Zheng and Knudsen, 1999;Linkenhoker et al, 2005). We wondered whether LMAN neurons in plastic birds, while showing suprathreshold selectivity for the new BOS, might still exhibit purely subthreshold responses to the previously preferred stimulus, namely the old BOS.…”
Section: Loss Of Subthreshold Responsiveness To the Original Song Aftmentioning
confidence: 99%
“…Experience-driven changes in the auditory space map are associated with corresponding changes in the topography of axonal projections from the ICC to the ICX (Feldman and Knudsen, 1997;DeBello et al, 2001) and with changes in patterns of both excitation and inhibition within the ICX (Zheng and Knudsen, 1999;Zheng and Knudsen, 2001).…”
Section: Introductionmentioning
confidence: 99%